Urgensi Pedoman Pemidanaan Demi Terwujudnya Putusan Hakim yang Berkeadilan - La Ode Faiki (Journal of Mandalika Literature, 2024)
Judge's decision, which is fair Abstract: In order to create a good and fair judiciary, the most important thing is to build the law as an instrument of legal institutions in order to carry out its duties as a law enforcement institution. Good law is law that supports justice and equality without discrimination. One of the mechanisms used by law enforcement institutions is a system of providing sanctions for those who violate legal norms. If it is related to criminal law enforcement, what must be developed is the construction and formulation of statutory regulations regarding criminal impositions, or in other words, the formulation of sentences in addition to reducing the scope for subjectivity in judges' judgments. One of the judge's decisions that caused concern for most of the public was when the judge tried a murder case committed by Inspector General Ferdy Sambo and his subordinates. They were all charged with violating Article 340 of the Criminal Code, but the judge who tried their case imposed varying sentences. This is because: The formulation of punishment in the Criminal Code Article 340 does not explicitly determine it basic punishment for each role. Criminal impositions vary only based on the judge's subjective judgment and beliefs. The formulation of Article 340 in the Criminal Code is: "Whoever deliberately and with premeditation takes the life of another person, is threatened with premeditated murder, with the death penalty or life imprisonment or for a certain period, a maximum of twenty years." The amount of authority given to judges by the State through Law No. 48 of 2009 concerning Judicial Power. In Article 1 "Judicial Power is the power of an independent state to administer justice to uphold law and justice based on Pancasila and the 1945 Constitution of the Republic of Indonesia, for the sake of the implementation of the Rule of Law of the Republic of Indonesia. This verse clearly states that judicial power is "independent" power. The word independence means that in adjudicating, assessing and deciding to impose a crime on someone, no intervention is permitted, unless their independence is put forward and firmly upheld. If we analyze the two statements above, what makes the judge's decision seem discriminatory or does not fulfill the elements of justice is due to the law/sentencing formula which provides an opportunity for the judge to make an unfair sentencing decision. Second, the judge has too much authority in assessing and deciding criminal cases in accordance with his considerations and beliefs.